Existence and uniqueness of solutions for nonlocal p-Laplacian problems - Behrouz, Emamizadeh; Amin, Farjudian (Department of Mathematics,Texas State University, 2016)
We study the existence and uniqueness of positive solutions to a class of nonlocal boundary-value problems involving the p-Laplacian. Our main tools are a variant of the Schaefer's fixed point theorem, an inequality which suitably handles the p-Laplacian operator, and a Sobolev embedding which is applicable to the bounded domain.